2017
DOI: 10.4236/ajps.2017.810171
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils from the Leaves and Flowers of <i>Callistemon viminalis</i>: Chemical Characterization and Evaluation of the Insecticide and Antifungal Activities

Abstract: The chemical compositions of the essential oils from the leaves and flowers of Callistemon viminalis and their insecticide and fungitoxic activities were determined. The essential oil was extracted by the hydrodistillation method using a modified Clevenger apparatus. The chemical characterization was performed by GC-MS and GC-FID. The evaluation of the insecticidal activity was performed with the Myzus persicae aphid, and the antifungal potential was determined via the inhibition of the mycelial growth of Alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…The chemical composition of the extracted essential oil reveals the presence of eucalyptol with higher percent area in GC-MS, beside alpha-Pinene and Alpha-terpineol were also important components, this result is match with previous studies (19,20), while Viridiflorol and its isomers appear in higher percent area than alpha-Pinene and alpha-Terpineol relative to the studies, which may indicate the different concentration of compounds present in Iraqi cultivated plant. Viridiflorol is an interesting natural compound show significant anticancer activity against cancer cells from lung, brain, and breast according to a novel study (21), also antioxidant, anti-inflammatory, and anti-mycobacterium activity were observed in recent study (22).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The chemical composition of the extracted essential oil reveals the presence of eucalyptol with higher percent area in GC-MS, beside alpha-Pinene and Alpha-terpineol were also important components, this result is match with previous studies (19,20), while Viridiflorol and its isomers appear in higher percent area than alpha-Pinene and alpha-Terpineol relative to the studies, which may indicate the different concentration of compounds present in Iraqi cultivated plant. Viridiflorol is an interesting natural compound show significant anticancer activity against cancer cells from lung, brain, and breast according to a novel study (21), also antioxidant, anti-inflammatory, and anti-mycobacterium activity were observed in recent study (22).…”
Section: Discussionsupporting
confidence: 88%
“…According to the study results, Callistemon viminalis essential oils have a good antimicrobial activity against Gram-positive bacteria, while no antifungal activity observed. The increase of essential oil quantity or using alcoholic diluent with different oil concentration not only the concentrate oil or increase the duration of exposure to oil may reveal or enhance the well-known inhibitory effect over fungal growth for the plant essential oil as in the studies (30,31). The results show good antibacterial activity of the oil against Grampositive bacteria, especially, on Streptococcus pneumoniae strain with inhibition zone comparable to that of vancomycin antibiotic drug, while the Gram-negative bacterial strains, Salmonella enteritidis, Pseudomonas aeruginosa, and Escherichia coli were not susceptible to the essential oil.…”
Section: Discussionmentioning
confidence: 99%
“…Another study on terpene antifungal activity has also suggested the synergic activity of terpene within plant extracts [ 46 ]. Although isolation and characterization of phytochemical content were not carried out in this study, based on studies by other researchers, secondary metabolites present in the DCM: methanol extract would have caused the observed effects [ 14 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenic attacks also caused metabolite and transcriptional changes in Medicago sativa (Suzuki et al 2005). When Sales et al (2017) compared alpha-pinene content of the flowers and leaves of Callistemon viminalis, the flowers contained 21.48% while the leaves only contained about 10.28%.…”
Section: Discussionmentioning
confidence: 99%